2014
DOI: 10.1002/pon.3611
|View full text |Cite
|
Sign up to set email alerts
|

Informing women with breast cancer about endocrine therapy: effects on knowledge and adherence

Abstract: Patients, especially older ones, can benefit from enhanced treatment information given additionally to routine care. Enhanced information about mode of action and potential side effects of endocrine therapy when included into clinical routine might foster patient autonomy and prevent early disruptions in adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 38 publications
(69 reference statements)
3
53
1
1
Order By: Relevance
“…Therefore, it may be essential that the clinicians are aware of signs and symptoms of depression in these women, providing the correct diagnosis, and offering appropriate therapy. This may be of importance in adherence to treatment and the cancer rehabilitation [46]. In this study however, there were no differences in demographic and treatment variables in the two groups of patients.…”
Section: Discussioncontrasting
confidence: 77%
“…Therefore, it may be essential that the clinicians are aware of signs and symptoms of depression in these women, providing the correct diagnosis, and offering appropriate therapy. This may be of importance in adherence to treatment and the cancer rehabilitation [46]. In this study however, there were no differences in demographic and treatment variables in the two groups of patients.…”
Section: Discussioncontrasting
confidence: 77%
“…If targeted appropriately, these factors are potentially modifiable and suggest an important role for providers in effectively communicating that adherence to ETs for the duration of treatment is an essential part of ensuring optimal breast cancer outcomes. Educational tools can potentially be useful in this setting by helping women understand the risks and benefits of ET, as well as by providing accurate information regarding side effects associated with ET [25]. Our analysis of a subsample of women (n 5 1,371) from the present research who completed a self-reported ET adherence measure 2 weeks after the initial assessment revealed high rates of adherence [26].…”
Section: Discussionmentioning
confidence: 90%
“…Increasing knowledge of side effects, communicating the benefits of the prescribed medication to improve adherence motivation, and identifying opportunities to resolve barriers to medication use (such as side effects) have been highlighted in reviews as critical components in a long-term adherence model in clinical practice (Accordino & Hershman, 2013; DiMatteo, Haskard-Zolnierek, & Martin, 2012). Oncology nurses can play an important role in informing patients about expected risk and side effects, which could prevent early disruptions in adherence (Heisig et al, 2015) and facilitate shared decision making. Additional tools, for use by physicians and other members of the oncology team (Taplin, Foster, & Shortell, 2013), are also needed to specifically assess and monitor symptoms before symptom burden becomes intolerable.…”
Section: Implications For Nursing and Intervention Opportunitiesmentioning
confidence: 99%